2000
DOI: 10.1379/1466-1268(2000)005<0347:aotloc>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the levels of conservation of the J domain among the various types of DnaJ-like proteins

Abstract: DnaJ-like proteins are defined by the presence of an approximately 73 amino acid region termed the J domain. This region bears similarity to the initial 73 amino acids of the Escherichia coli protein DnaJ. Although the structures of the J domains of E coli DnaJ and human heat shock protein 40 have been solved using nuclear magnetic resonance, no detailed analysis of the amino acid conservation among the J domains of the various DnaJ-like proteins has yet been attempted. A multiple alignment of 223 J domain seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(51 citation statements)
references
References 21 publications
1
48
0
2
Order By: Relevance
“…DnaJ proteins deliver polypeptide substrates to Hsp70 chaperones for processing and regulate chaperone activity via the interaction of their J domains with their Hsp70 partners (Bukau and Horwich, 1998;Walter and Buchner, 2002). The J domain in nearly all known DnaJ and DnaJ-like proteins contains a central His-Pro-Asp (HPD) motif, which is believed to be crucial for the interaction between the J domain and Hsp70 (Hennessy et al, 2000). However, this motif is not fully preserved in the J domains of ARC6 and its orthologs, because only the central Pro is conserved uniformly (Figure 3).…”
Section: Arc6 and Its Orthologs Encode J-domain Proteins Unique To Plmentioning
confidence: 99%
See 1 more Smart Citation
“…DnaJ proteins deliver polypeptide substrates to Hsp70 chaperones for processing and regulate chaperone activity via the interaction of their J domains with their Hsp70 partners (Bukau and Horwich, 1998;Walter and Buchner, 2002). The J domain in nearly all known DnaJ and DnaJ-like proteins contains a central His-Pro-Asp (HPD) motif, which is believed to be crucial for the interaction between the J domain and Hsp70 (Hennessy et al, 2000). However, this motif is not fully preserved in the J domains of ARC6 and its orthologs, because only the central Pro is conserved uniformly (Figure 3).…”
Section: Arc6 and Its Orthologs Encode J-domain Proteins Unique To Plmentioning
confidence: 99%
“…However, this motif is not fully preserved in the J domains of ARC6 and its orthologs, because only the central Pro is conserved uniformly (Figure 3). Conversely, other residues hypothesized to be essential for J-domain structure (Hennessy et al, 2000) are conserved (Figure 3), and a database search based on 3D-PSSM protein structure predictions (http://www. sbg.bio.ic.ac.uk/servers/3dpssm/) (Kelley et al, 2000) showed a very good fit between the ARC6-like J domains and the experimentally determined crystal structures of the J domains from human HSP40 and E. coli DnaJ.…”
Section: Arc6 and Its Orthologs Encode J-domain Proteins Unique To Plmentioning
confidence: 99%
“…In fact, Hdj1 is even more effective than Hdj2 in refolding luciferase in vitro (54). In general, type I and type II J proteins have a more highly conserved J domain within their own groups and tend to interact with a broader range of substrates, whereas type III J proteins, have a lower level of conservation and a more restricted substrate specificity (55). A broad substrate specificity would be expected if ERdj4 played a role in either the refolding of proteins or the retro-translocation of unfolded proteins during ER stress.…”
Section: Fig 3 Subcellular Localization Of Ha-tagged Erdj4mentioning
confidence: 99%
“…According to the homology of the DnaJ protein of E.coli, Hsp40 proteins were classified into three types: Type I DnaJ proteins (DnaJA) possess all four parts of DnaJ protein in E. coli; Type II DnaJ proteins (DnaJB) possess the N-terminus Jdomain and the glycine/phenylalanine-rich region; Type III DnaJ proteins (DnaJC) only have a J-domain, which is not necessarily located at N-terminus of the protein [11,12]. Recently, type IV DnaJ protein family was added, which differs from the other three types of DnaJ proteins in that it owns a 'J-like' domain [6,13,14] containing various mutations in a highly conserved histidine, proline, and aspartic acid-HPD motif located between helices II and III in DnaJ domain [6,[15][16][17]. However, Peter Walsh et al (2004) proposed that the term J-proteins should be used more strictly to describe only J proteins with well-conserved Jdomain in the HPD motif, while structurally less-conserved proteins should be referred to as J-like proteins [6].…”
Section: Introductionmentioning
confidence: 99%